A identidade profissional do pedagogo no curso de pedagogia da UFPA e nas diretrizes curriculares nacionais: aproximações e distanciamentos - CAMPOS, Helane Cibele do Nascimento (2009)
This research focuses on the proposal of the current Pedagogic political project’s professional identity of the Universidade Federal do Pará (Campus Belém), relating it with the professional identity which is indicated in the Diretrizes Curriculares Nacionais for the Education course, that happened in 2006, and trying to identify the similarities and the distances that exist among the presents proposals of identity in these curriculos orientations. The study could investigate the identity that professional makes part of, my own identity constitution, from my own admission in Education course at Universidade Federal do Pará, it contributes to the discussion about curriculos orientations of the Education courses in Brazil, and in this way, it strengthens the set of studies which have already been carried out and in the process of the investigation at Instituto de Ciêmcias da Educação da UFPA, about Education course – it not only added the efforts undertook but others Brazilian researchers and professional associations that investigate about the professional identity of the Educationalist. The methodological and theoretical route of this research got its inspiration in the presented cathegories by Dubar – like: professional identity of the base, inherited identity and focus identity – it has been developed through the collection and analysis of the documents which are related to the two curriculos that are mentioned, orientations aiming identity in the Projeto Político Pedagógico of the Education course of UFPA and indicated in the Diretrizes Curriculares Nacionais of the Education course. For the summary, I selected paths of the collected material, I selected paths of the construction of the professional identity of the Educationalist’s profile, the curriculo organization; and the course duration. In each of these pathes I tried to identify the similarities and distances between both curriculo orientations in analysis in these study, I reflected about important aspects like: teaching, management, and locus of the formation of the Educationalist professional and his reconfigurations in the context of the present educational politics.